Silica-Supported Glyoxylic Acid: A Traceless, Green Approach to the Groebke–Blackburn–Bienymé Reaction - Surkar, Pritam; Kaur, Tanpreet; Sharma, Anuj (Synlett, 2015)
The first example of a formaldehyde equivalent covalently immobilized onto a silica surface is presented in a prototypical regioselective Groebke–Blackburn–Bienymé (GBB) reaction to afford 2-unsubstituted-3-aminoimidazo[1,2-a]heterocycles. The presence of a solid support facilitates the reaction without a solvent under microwave irradiation in good yields.
Keywords: silica-supported glyoxylic acid; isocyanide; multicomponent reactions; solventless